Independent and complementary bio-functional effects of CuO and Ga2O3 incorporated as therapeutic agents in silica- and phosphate-based bioactive glasses - Tite, T. (2022)
The incorporation of therapeutic-capable ions into bioactive glasses (BGs), either based on silica (SBGs) or phosphate (PBGs), is currently envisaged as a proficient path for facilitating bone regeneration. In conjunction with this view, the single and complementary structural and bio-functional roles of CuO and Ga2O3 (in the 2–5 mol% range) were assessed, by deriving a series of SBG and PBG formulations starting from the parent glass systems, FastOs®BG – 38.5SiO2—36.1CaO—5.6P2O5—19.2MgO—0.6CaF2, and 50.0P2O5—35.0CaO—10.0Na2O—5.0 Fe2O3 (mol%), respectively, using the process of melt-quenching. The inter-linked physico-chemistry – biological response of BGs was assessed in search of bio-functional triggers. Further light was shed on the structural role – as network former or modifier – of Cu and Ga, immersed in SBG and PBG matrices. The preliminary biological performance was surveyed in vitro by quantification of Cu and Ga ion release under homeostatic conditions, cytocompatibility assays (in fibroblast cell cultures) and antibacterial tests (against Staphylococcus aureus). The similar (Cu) and dissimilar (Ga) structural roles in the SBG and PBG vitreous networks governed their release. Namely, Cu ions were leached in similar concentrations (ranging from 10–35 ppm and 50–110 ppm at BG doses of 5 and 50 mg/mL, respectively) for both type of BGs, while the release of Ga ions was 1–2 orders of magnitude lower in the case of SBGs (i.e., 0.2–6 ppm) compared to PBGs (i.e., 9–135 ppm). This was attributed to the network modifier role of Cu in both types of BGs, and conversely, to the network former (SBGs) and network modifier (PBGs) roles of Ga. All glasses were cytocompatible at a dose of 5 mg/mL, while at the same concentration the antimicrobial efficiency was found to be accentuated by the coupled release of Cu and Ga ions from SBG. By collective assessment, the most prominent candidate material for the further development of implant coatings and bone graft substitutes was delineated as the 38.5SiO2—34.1CaO—5.6P2O5—16.2MgO—0.6CaF2—2.0CuO—3.0Ga2O3 (mol%) SBG system, which yielded moderate Cu and Ga ion release, excellent cytocompatibility and marked antibacterial efficacy.